A randomised comparison of the Ambu® AuraGain™ and the LMA® supreme in infants and children. (9th December 2015) - Jagannathan, N.; Hajduk, J.; Sohn, L.; Huang, A.; Sawardekar, A.; Gebhardt, E. R.; Johnson, K.; De Oliveira, G. S.
Summary: We conducted a randomised trial in 100 children in order to compare the clinical performance of the Ambu ® AuraGain ™ and the LMA ® Supreme * for airway maintenance during mechanical ventilation. The primary outcomes were initial and 10‐min airway leak pressures. Ease, time and success rates for device and gastric tube insertion, fibreoptic grades of view, airway quality during anaesthetic maintenance, and complications were also assessed. There were no differences in the initial and ten min airway leak pressures between the Ambu AuraGain and LMA Supreme, median (IQR [range]) initial: 19 (16–22 [10–34]) vs 18 (14–24 [8–40]) cmH2 O, p = 0.4; and ten min: 22 (18–26 [11–40]) vs 20 (16–26 [12–40]) cmH2 O, p = 0.08, respectively. Ease, time and success rates for device placement, gastric tube insertion and complications were also not significantly different. Children receiving the LMA Supreme required more airway manouevers (7 vs 1 patient, p = 0.06) to maintain a patent airway. Our results suggest that the Ambu AuraGain may be a useful alternative to the LMA Supreme, as demonstrated by comparable overall clinical performance in children.